Contested constructions of trust in the juridical system of Argentina. Issue 3 (2nd September 2018) - Rohrer, Ingo
Abstract: In 2014 the Attorney General of Argentina opened the pathway to install local offices in urban slums to facilitate access to the juridical system for the most underserved sectors of society. The initiative, ATAJO - the Territorial Agency for Access to Justice, attempts to strengthen civic rights, explore social prevention of crime, and build trust-based relations with state bureaucracy. Using the example of the ATAJO office in the informal settlement Villa 1-11-14 in Buenos Aires, I trace how legal actors carefully attempt to develop trust-based relations. I show how their practices of trust building correspond to how the legal professionals themselves perceive the institution they are representing and how this perception then shapes their actions.